Being well at work: the impact of organizational climate and social identity on employee stress and self-esteem over time. Issue 3 (4th May 2019) - Willis, Loren; Reynolds, Katherine J.; Lee, Eunro
ABSTRACT: In organizational psychology, staff perceptions of organizational climate have been found to be an important predictor of employee outcomes, such as employee stress. However, only a small pool of research has investigated the psychological mechanism that underpins the relationship, and no past literature has explored how the relationship persists over time. This paper uses the social identity approach to investigate whether social identification predicts and mediates the relationship between staff perceptions of organizational climate and their levels of stress and self-esteem over time. Employing a sample of public school teachers, the study was conducted over two years (N = 281, 65 schools). The results indicated that social identification fully mediated the relationship between organizational climate and self-esteem longitudinally but showed no significant relationship with stress. The implications of these findings are discussed, with recommendations for future research.